On the greatest happiness for the greatest number: beyond Anderson Woods’ 1925 opposition - Terence Rajivan Edward (IJRDO - Journal of Social Science and Humanities Research, 2025)
This paper responds to Anderson Woods’ famous paper against Jeremy Bentham’s use of the formula: the greatest happiness for the greatest number. (Or of the greatest number: no distinction made here.) I reject two objections that Woods makes: that the formula, taken literally, specifies two final ends when the intention was to specify one; and that these ends are inconsistent. Both fail because the ends extracted are incorrect and a correct extraction does not fail to specify a final and consistent end. Then I make my own objection: that the formula is misleading at best, because utility monsters, as they are today called, count for more when the aim is maximizing the happiness in the world.